Does the use of a piezoelectric saw improve neurosensory recovery following sagittal split osteotomy?. Issue 3 (March 2022) - Sobol, D.L.; Hopper, J.S.; Ettinger, R.E.; Dodson, T.B.; Susarla, S.M.
Abstract: Neurosensory disturbance of the inferior alveolar nerve (IAN) is an adverse effect associated with sagittal split osteotomies (SSO). The purpose of this work was to evaluate neurosensory recovery of the IAN when SSOs were performed with piezoelectric (PZ) versus reciprocating (RP) saws. This was a prospective split-mouth study of patients undergoing bilateral SSO using a PZ saw on one side and an RP saw on the other. The primary outcome of interest was neurosensory recovery, as assessed using the functional sensory recovery (FSR) scale defined by the UK Medical Research Council. Descriptive, bivariate, and regression statistics were computed. Twenty patients (40 SSOs) with a mean age of 19.9 ± 3.2 years were included. The mean mandibular movement did not differ significantly ( P = 0.50) between the PZ and RP groups. All patients achieved FSR within 1 year of surgery (range 34–249 days). The median time to FSR overall was comparable between the PZ and RP groups (94.5 days and 101.5 days, respectively; P = 0.20). However, at the time FSR was achieved, PZ SSO sites were more likely to have higher neurosensory scores when compared to RP SSO sites (hazard ratio 2.3, 95% confidence interval 1.1–4.9, P = 0.04).